A rare case of polyorchidism in a 48-year-old man with inguinal hernia - Valente, Tania; Ferreira, Nuno; Ferreira, Gonçalo; Figueiredo, Arnaldo; Bárbara, Patrícia; Aniceto, Cristina; Marinho, Ricardo; Santos, Miguel C.; Eufrásio, Pedro (International Surgery Journal, 2022)
Polyorchidism is a rare congenital anomaly characterized by the presence of more than two testes. Triorchidism is the most common variant. Polyorchidism has been reported in around two hundred cases in the world to date. It is usually diagnosed incidentally in routine exams or surgery. It can be associated with undescended testis (40%), hernia (30%), and torsion (15%), among others. Given how rare it is, polyorchidism requires a high degree of suspicion. The exact aetiology of polyorchidism is unknown. The preservation of supernumerary testis has been controversial. Today, in the absence of pain, conservative management with a strict ultrasound and magnetic resonance imaging (MRI) follow-up is the most widely used approach. We present a case of a 48-year-old man who had a personal history of left cryptorchidism and came to our appointment with a bilateral inguinal hernia. During surgery for hernia repair, we found a supernumerary testis located on the left inguinal region with no epididymis or vas deferens. We opted for orchidopexy. In the other left testis, we did an orchidectomy due to the presence of a suspicious nodule. The histology was negative for neoplasia.